Influence of water treatment on digestion dynamics of steers consuming high- and low-forage diets - D.L. Harmon; A.D. Flood (Kansas Agricultural Experiment Station Research Reports, 1991)
The influence of drinking water treatment (Oxion Inc., Hugoton, KS) on digestion and metabolism was evaluated in steers fed low- and high-forage diets. Water treatment did not influence digestibility of any nutrient measured nor did it influence the profile of ruminal metabolites. Water treatment did increase water consumption two- to threefold and also increased ruminal fractional water outflow (%/h) for steers fed the high forage, but not the high concentrate, diet. Increased water consumption could be a beneficial response, but it is not known if water consumption increases with management programs different than those used in the present study.
Keywords: Cattlemen& #x27; s Day; 1991; Kansas Agricultural Experiment Station contribution; no. 91-355-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 623; Beef; Steer; Water; Digestibility; Intake; Rumen